PENGARUH KOMPETENSI SOSIAL GURU TERHADAP MOTIVASI BELAJAR SISWA KELAS XI JURUSAN AKUNTANSI SMK NEGERI - Sandra Fitria Wardani; Maria Ulfah; Okianna Okianna (Universitas Tanjungpura, 2018)
AbstractThis study attempts to ascertain whether there are the influence and how big the influence of social competence they think of the motivation to study grader XI student of accounting of SMKN 7 Pontianak. The form of this research is quantitative research with the kind of research ex-post facto. Samples to this research is student of grade XI of accounting of SMKN 7 Pontianak the school year with the number of 64 student. A method of the sample collection too was Stratiffied Proportional Random Sampling. Data collected by the questionnaire that has been tested validity and reability. Data analysis technique that is used is the program SPSS volume.18. The result of this research shows that after do linear regression simple on the variables of x and y be said that competence social have a negative influence on the motivation to study the student with the regression equation is 23%. With do the hypothesis and obtained value significance of 0,000<0,05. So that it can be concluded that ( h0 ) will be rejected and (ha) were received which would mean there are the influence of social competence between “they think of the motivation to study students” Keywords: Social competence teachers, The motivation to study students